Rancang Bangun Media Pembelajaran Pengenalan Hewan Nokturnal Untuk Anak Autisme - Sriayuwahyuni, Putri; Sutedi, Ade; Latifah, Ayu; Fitriani, Leni (Jurnal Algoritma, 2025)
Children with autism often experience difficulties in focusing, communicating, and processing abstract information, making conventional learning methods less effective. This requires learning media that can accommodate special needs through visual, auditory, and exploratory approaches. This study aims to design and develop Android-based interactive learning media to introduce nocturnal animals to children with autism. The method used is the Multimedia Development Life Cycle (MDLC), which consists of the stages of concept, design, material collecting, assembly, testing, and distribution. This media has two main features, namely “Learn,” which presents text, images, sounds, and voice-overs, and “Puzzle,” which trains children's memory and fine motor skills through animal picture assembly activities. Testing results through alpha testing using the black-box method showed that all application features ran according to design without errors. The implication of this research is the availability of learning media that is more interactive, enjoyable, and suitable for the characteristics of children with autism, thus providing an innovative alternative in supporting their learning process.